Balanced Nutrition Education Based on the "Isi Piringku" Principle at the Outpatient Clinic of Rokan Hulu Regional General Hospital: A Promotive Effort in the Prevention of Non-Communicable Diseases - Refa Rahmaddiansyah; Sukarsi Rusti; Maria Nurlita; Afridel Fiane; Hertaria Yosephine Rajagukguk (Majalah Ilmiah METHODA, 2026)
Non-communicable diseases (NCDs) such as diabetes mellitus, hypertension, and obesity constitute a significant public health problem in Indonesia. One of the principal modifiable risk factors is an unhealthy dietary pattern. Balanced nutrition education based on the "Isi Piringku" principle represents a promotive strategy to improve nutrition literacy in the community. This activity aimed to enhance the knowledge and understanding of patients and their family members attending the Outpatient Clinic of Rokan Hulu Regional General Hospital regarding the principles of balanced nutrition and the application of the "Isi Piringku" concept in daily life. The education session was conducted on September 8, 2025, through a visual presentation using PowerPoint media explaining the "Isi Piringku" principle, followed by a discussion and question-and-answer session with healthcare personnel. Evaluation was carried out qualitatively through observation of participant engagement throughout the activity. The activity demonstrated active participant involvement during the discussion session, with various questions and responses reflecting interest in and comprehension of the material. The visual and interactive approach was considered capable of improving participants’ information retention. Nutrition education using a visual and participatory approach may represent a relevant method for implementation in healthcare facilities as part of a promotive strategy for NCD prevention. In the future, quantitative measurement is required to evaluate the long-term impact of similar interventions.